(untitled) (Research, Society and Development, 2021)
The aim of this study was to establish the profile of absenteeism due to health problems among professionals at a university hospital in Sergipe. This is a descriptive, cross-sectional and quantitative study, carried out with all professionals at a university hospital in Aracaju/SE. The survey was conducted in May 2020, based on data from the computerized Management Information system (IG) and electronic files from the Occupational Health and Safety at Work (SOST) sector. All absences due to health problems, valid between January and December 2019, were included, from which information was collected on gender, number of days lost, position, expenses with leave and the cause according to the International Classification of Diseases – 10th revision. Data were grouped in Microsoft Excel 2013 and analyzed using the R Core Team 2018 software. 2,053 certificates were observed; equivalent to 5,620.50 lost workdays and a financial cost of R1,075,098.93. The professionals with the highest number of certificates were nursing technicians (50.2%) and female (83.92%). The main causes were diseases of the respiratory system (17.7%), infectious and parasitic diseases (14.8%) and diseases of the musculoskeletal system and connective tissue (12.2%). It is concluded that absenteeism reflects occupational exposures, especially by health professionals. This study can contribute to the development of health promotion and disease prevention strategies resulting from the work of these professionals.